Proportional–integral–derivative/fuzzy sliding mode control for suspension of active magnetic bearing system. (December 2017) - Su, Te-Jen; Li, Tsung-Ying; Tsou, Tung-Yeh; Giap, Van-Nam; Nguyen, Quang-Dich
In this article, we focus on a suspension active magnetic bearing system that majorly experiences many disturbances. First, we construct a complete model of a suspension active magnetic bearing system composed of conventional proportional–integral–derivative controllers with two kinds of inputs and a robust control method, known as the sliding mode control method. On certain proportional–integral–derivative controllers, the sliding mode control method is used to control linear or nonlinear systems while a chattering phenomenon occurred in each time period. This chattering is due to the high-frequency characteristic of this control method, but it was represented a major disadvantage. Therefore, we propose these techniques for reducing much of this chattering, and then we also propose a fuzzy controller as the control model. In regard to the sliding mode, the fuzzy controller of input and output signals approximates the signals of the proportional–integral–derivative and sliding mode control controller outputs. We also replace the signum function from the saturation function and use the MATLAB Simulink programming environment in our design work. Finally, we compare the average and maximum tracking errors with those of a method proposed by Lin et al. and find that the results of our proposed control method tracks very well with the sinusoidal input signal and also much better than the other method.